2019
DOI: 10.56093/ijas.v89i10.94588
|View full text |Cite
|
Sign up to set email alerts
|

Antityrosinase activity and photosynthetic pigments in seaweed treated sprouts of Vigna aconitifolia

Abstract: The seaweed, Ascophyullum nodosum is the focus of the research these days and is looked upon as an important alternative bio-fertilizer. For this purpose the interaction of the seaweed with different plants including legumes is important to understand. We previously noticed lesser pigmented nodules in legume plant Vigna aconitifolia, when grown in presence of A. nodosum Extract (ANE). We therefore studied the effect of the ANE on the tyrosinase inhibition activity, an enzyme known to produce melanin pigment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Synthesis of nanoparticles from weeds has drawn more attention because of inexpensive, nonpathogenic, sustainable and quick single step process. The plant extract have natural tendency to reduce and stabilize silver ions because of presence of a number of biomolecules like terpens, tannins, alkaloids, phenolics, aminoacids, saponins and vitamins [20] . A large number of weeds are reported that reduce reduced silver ions and its importance (Table 1).…”
Section: Synthesis Of Silver Nanoparticles Using Weeds As Plant Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of nanoparticles from weeds has drawn more attention because of inexpensive, nonpathogenic, sustainable and quick single step process. The plant extract have natural tendency to reduce and stabilize silver ions because of presence of a number of biomolecules like terpens, tannins, alkaloids, phenolics, aminoacids, saponins and vitamins [20] . A large number of weeds are reported that reduce reduced silver ions and its importance (Table 1).…”
Section: Synthesis Of Silver Nanoparticles Using Weeds As Plant Extractmentioning
confidence: 99%
“…The synthesis of nanoparticles from ecofriendly material like plant parts (root, stem, leaf), algae, fungi, bacteria have many sustainable use and harmonious to biomedical as well as pharmaceutical applications because in this no harmful chemical is used in the protocol of nanoparticle synthesis. In all emergent area of research i: e physical, chemical and biological sciences nanoparticles have great use [20] . In many areas nanoparticle gaining attention such as biomedicines, cosmetics, drug delivery, healthcare, eco environment, food and feed, water disinfectant, antimicrobial filter, wound dressing material, air filtration, sensor etc.…”
Section: Introductionmentioning
confidence: 99%